The Factor VIII Bypassing Activity of Prothrombin Complex Concentrates: The Roles of Factor VIla and of Endothelial Cell Tissue Factor - Teitel, Jerome M (Thrombosis and Haemostasis, 1991)
An experimental model incorporating cultured endothelial cells (EC) was used to study the "factor VIII bypassing" activity of prothrombin complex concentrates (PCC), a property exploited in the treatment of hemophiliacs with alloantibodies to factor VIII. Two PCC preparations were ineffective as stimuli of tissue factor expression by EC. However, incubation with a combination of PCC plus endotoxin (lipopolysaccharide, LPS) or tumor necrosis factor (TNF) induced much greater tissue factor expression than was seen in response to either substance alone. PCC expressed an additional direct procoagulant activity at the EC surface, which could not be attributed to either thrombin or factor Xa, and which was diminished by an anti-tissue factor antibody. Therefore factor VIIa, which was detectable in both PCC preparations, likely provided this additional direct procoagulant activity at the EC surface. We also excluded the possibility that coagulation proteases contained in or generated in the presence of PCC are protected from inactivation by AT III. Therefore, PCC can indirectly bypass factor VIII by enhancing induced endothelial tissue factor expression, and also possess direct procoagulant activity, probably mediated by factor VIIa.